Outcome of surgical untethering of tethered cord syndrome in adults due to spina bifida occulta - Arkawazi, Bassam Mahmood Flamerz (AL-Kindy College Medical Journal, 2019)
Background:. Children with spina bifida occulta require early surgery to prevent neurological deficits. The treatment of patients with a congenitally tethered cord who present in adulthood remains controversial. Objective: The aim of this study is to describe the outcome obtained in 61 adult patients with congenital TCS and no prior surgical treatment who underwent surgical untethering. Methods: This prospective study was conducted on 61 adult patients who underwent surgical untethering for spina bifida occulta at four neurosurgical centers in Baghdad / Iraq between March 2000 and January 2018. Patients who had undergone prior myelomeningocele repair or tethered cord release surgery were excluded. The most common intraoperative findings were lipomyelomeningocele (41%) and a tight terminal filum (36%). The follow-up duration ranged from 10.8 to 149.5 months (mean 20.9 months). Of the 34 patients with back pain, status improved in 65%, worsened in 3%, remained unchanged in 18%, and improved and later recurred in 15%. Lower-extremity pain improved in 16 patients (53%), remained unchanged in 23%, improved and then recurred in 17%, and worsened in 7%. Lower-extremity weakness improved in 47%, remained unchanged in 47%, and improved and then recurred in 5%. Finally, of the 17 patients with lower-extremity sensory changes, status improved in 35%, remained unchanged in 35%, and the information on five patients was unavailable. Surgical complications included three wound infections, one cerebrospinal fluid leak, and two pseudomeningoceles requiring surgical revision. One patient developed acute respiratory distress syndrome and sepsis postoperatively and died several days later. Conclusions: Adult-age presentation of a congenital tethered cord is unusual. Despite a slight increase in postoperative neurological injury in adults, surgery has relatively low risk and offers good potential for neurological improvement or stabilization. As in children, we recommend early surgery in adults with this disorder. The decision to undertake surgery, however, should be modulated by other factors such as a patient’s general medical condition and risk posed by anesthesia.